Synthesis and Study the Anti-Bacterial Effect of New Oxazepine Derivatives - Fatima Jabbar Hassoun; Mohammed Fadhil Hassan; Muqdad Irhaeem Kadhim (OBAT: Jurnal Riset Ilmu Farmasi dan Kesehatan, 2025)
in this study was preparation heterocyclic compounds of seven ring know Oxazepine compounds through reaction of schiff base compounds with cyclic anhydride (malic anhydride), schiff bases compounds synthesis by reaction between amins and different aldehyde compounds and the prepared compounds were identification by infrared (IR). The biological activity of the prepared compounds was studied and its effect on two bacteria (Escherichia coli)positive bacteria and (Staphylococcus aureus) negative bacteria.